Endothelial Jag1-RBPJ signalling promotes inflammatory leucocyte recruitment and atherosclerosis. Issue 2 (5th August 2016) - Nus, Meritxell; Martínez-Poveda, Beatriz; MacGrogan, Donal; Chevre, Rafael; D'Amato, Gaetano; Sbroggio, Mauro; Rodríguez, Cristina; Martínez-González, José; Andrés, Vicente; Hidalgo, Andrés; de la Pompa, José Luis
Abstract : Aim: To determine the role of NOTCH during the arterial injury response and the subsequent chronic arterial-wall inflammation underlying atherosclerosis. Methods and results: We have generated a mouse model of endothelial-specific ( Cdh5 -driven) depletion of the Notch effector recombination signal binding protein for immunoglobulin kappa J region (RBPJ) [( ApoE −/− ); homozygous RBPJk conditional mice ( RBPJ flox/flox ); Cadherin 5-CreERT, tamoxifen inducible driver mice ( Cdh5-Cre ERT )]. Endothelial-specific deletion of RBPJ or systemic deletion of Notch1 in athero-susceptible ApoE −/− mice fed a high-cholesterol diet for 6 weeks resulted in reduced atherosclerosis in the aortic arch and sinus. Intravital microscopy revealed decreased leucocyte rolling on the endothelium of ApoE −/− ; RBPJ flox/flox ; Cdh5-Cre ERT mice, correlating with a lowered content of leucocytes and macrophages in the vascular wall. Transcriptome analysis revealed down-regulation of proinflammatory and endothelial activation pathways in atherosclerotic tissue of RBPJ- mutant mice. During normal Notch activation, Jagged1 signalling up-regulation in endothelial cells promotes nuclear translocation of the Notch1 intracellular domain (N1ICD) and its physical interaction with nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB). This N1ICD–NF-κB interaction is required for reciprocal transactivation of target genes, including vascular cell adhesion molecule-1 . Conclusions: Notch signalling pathway inactivation decreases leucocyte rolling, thereby preventing endothelial dysfunction and vascular inflammation. Attenuation of Notch signalling might provide a treatment strategy for atherosclerosis.